Straightforward, safe, and efficient interlocking screw insertion during intramedullary nailing using a Steinmann pin and hammer: a comparative study - Maria Florencia Deslivia; Hee-June Kim; Sung Hun Kim; Suk-Joong Lee (The Ewha Medical Journal)
Objectives: Accurately targeting distal nail holes and placing distal interlocking screws pose challenges during intramedullary nailing. This study proposes a straightforward technique for distal locking screw insertion using a Steinmann pin, eliminating the need to reposition the pin or drill bit.